Challenges and lessons learned in promoting adoption of standardized local public health service delivery data through the application of the Public Health Activities and Services Tracking model - Bekemeier, Betty; Park, Seungeun; Whitman, Greg (Journal of the American Medical Informatics Association : JAMIA, 2019)
Population-level prevention activities are often publicly invisible and excluded in planning and policymaking. This creates an incomplete picture of prevention service-related inputs, particularly at the local level. We describe the process and lessons learned by the Public Health Activities and Services Tracking team in promoting adoption of standardized service delivery measures developed to assess public health inputs and guide system transformations. The 3 factors depicted in our Public Health Activities and Services Tracking model-data need and use, data access, and standardized measures-must be realized to promote collection of standard public health system data. Bureaucratic, resource, system, and policy challenges hampered our efforts toward adoption of the standardized measures we promoted. Substantial investments of time, resources, and coordination appear necessary for systems to adopt changes needed for collecting comparable service delivery data. Lessons from our process of promoting adoption of standardized measures provide recommendations to support future efforts to measure public health system contributions to the public's health.